The techniques of memorization music pieces: a case study of students of Faculty of Music Shah Alam / Mohd Rizal Mohd Man Sha - Mohd Man Sha, Mohd Rizal (2013)
This study was conduct to explore techniques of memorization music piece a case study UiTM faculty of music Shah Alam. The purpose of this study to identify how music students perceive the important memorizing, to find out the best way for memorizing the music piece and to identify the benefits of memorizing techniques. For this particular study, this study will use the quantitative method in order to gather opinions from a large group of the student in UiTM needed regarding the specific topic of this study. The purpose of choosing this method is to gain more information about the technique of memorization music piece used by music students. From the findings, the data analysed and discussed are classified into three sections according to the sections divided by the researcher for the questionnaire, to answer research questions of this study. Therefore, the finding of this study is also categorized into these three sections which are how do the students perceive the importance of memorizing music piece, how do the students perform by memory and what are the benefits of memorizing music piece for the students